¿Cómo prolongar el realismo hoy? (2010)
This work investigates what is the philosophical realism. It offers a synthesis of what has been the realistic philosophy up to today regarding his discovery of the diverse senses of the act: Pure act; act of being created; intellect agent; cognitive innate and acquired habits; immanent cognitive operations; virtues of the will; acts of wanting. After that; it he proposes who it is possible to progress nowadays in the realism: discovering other senses of the act.